Modern researches of apocalyptic thematics in the work of domestic and foreign bibles - Maria Bardyn (Cхід, 2018)
Apocalyptic problems were relevant throughout the development of Christian culture. The content of apocalyptic works consisted mainly of eschatological revelations, that is, prophecies concerning the future of the end of the world.